Proposal to accelerate the visiting regim processes - García Flores, Miguel Ángel (2021)
When a father or mother resort to the court, in order to get days to be established to visit their daughter or son, given the impossibility of reaching an agreement; It would not have to delay in being resolved the controversy on the part of the Judge, with the expedition of the corresponding sentence; since it is not a complicated Litis. Those who are involved in the processing of this type of judicial process, be they defendants or operators of the law, warn that these processes can last years in the first instance until it is resolved, increasing the uncertainty when it is appealed and has to be reviewed by the Superior Hierarchical, in this case the Civil or Family Chamber, as appropriate. In this article it is intended, without making legislative modifications, with the existing legal weapons, to make the Visitation Processes more efficient, for the benefit of the child or adolescent, since it is their right to maintain the filial bond with his father or mother.